A Comparative Study of the Effect of Dexmedetomidine and Nalbuphine as an Adjuvant to Levobupivacaine in Ultrasound-Guided Supraclavicular Brachial Plexus Block: A Prospective Randomized Double-Blind Study - Jyoti Mala; Sudha Singh; Pankaj Kumar; Arvind Kumar (Journal of Pharmacy and Bioallied Sciences)
Background: The supraclavicular brachial plexus block (SCBPB) demonstrates wide surgical use for upper limbs through its application of levobupivacaine as the chosen local anesthetic because it offers lower cardiotoxic effects. Patients benefit from adjuvant medications dexmedetomidine and nalbuphine since these compounds increase blockade sustainability and enhance characteristics of the block. Materials and Methods: The research investigated 60 patients with upper limb surgery that received ultrasound-guided SCBPB. The study design was prospective randomized double-blind. The research participants were divided into two groups of 30 each: Group D used 30 ml of 0.5% levobupivacaine with dexmedetomidine set at 50 μg, and Group N applied 30 ml of 0.5% levobupivacaine with nalbuphine at 10 mg. The authors analyzed and compared the block onset time along with the duration of sensory and motor block activity and analgesic period as well as hemodynamic changes and adverse effects between both groups. Results: The participants in Group D experienced faster sensory block onset times that were statistically lower than those observed in Group N with 7.5 ± 1.2 minutes versus 9.2 ± 1.4 minutes (P < 0.05). The time for motor block to take effect exhibited the same pattern as sensory block establishment. The subjects in Group D demonstrated longer blocks compared to subjects in Group N regarding sensory preservative time and motor preservative time [(sensory: 720 ± 30 min, motor: 680 ± 25 min) versus (sensory: 580 ± 35 min, motor: 540 ± 30 min)] (P < 0.05). The subjects in Group D received an extended duration of analgesic effects (850 ± 40 minutes) than those in Group N (660 ± 45 minutes) (P < 0.05). The subjects in both groups maintained stable hemodynamic conditions yet experienced mild bradycardia in Group D and mild sedation in Group N. The study revealed no severe adverse occurrences between any groups. Conclusion: Dexmedetomidine along with nalbuphine made levobupivacaine more effective in SCBPB, yet dexmedetomidine created longer-lasting effects on sensory and motor block while providing prolonged analgesic benefits.